La construcción de la imagen exterior de España desde su política cultural - Cano Jiménez , Gema (Mediaciones Sociales, 2009)
This short work, which is presented here, belongs to a bigger study where I analyse the cultural clichés about Spain from three points of view: the first, the cliché generated by ourselves. The second, the commonplaces generated from outside, specially from foreign literature and journalism. Finally, in the last part, I analyse if the present cultural policies try to overcome these clichés, or if on the contrary, they reproduce them, or if in a third way, these policies are building new ones such as our modernization. The following essay is a brief summary of the third aforementioned part: an approach to the current policy action of the Spanish state orientated to go beyond our old cliches. This overcoming seems to be indispensable to achieve other goals such as the economic ones. In this way, this article is not strictly an analysis of the cultural politics current Spanish, but on the instruments and intentions of the same one to create a new image of the country with a view to the exterior.